HCV and tumor-initiating stem-like cells - Machida, Keigo (Frontiers in Physiology, 2022)
Neoplasms contain tumor-initiating stem-like cells (TICs) that are characterized by increased drug resistance. The incidence of many cancer types have trended downward except for few cancer types, including hepatocellular carcinoma (HCC). Therefore mechanism of HCC development and therapy resistance needs to be understood. These multiple hits by hepatitis C virus (HCV) eventually promotes transformation and TIC genesis, leading to HCC development. This review article describes links between HCV-associated HCC and TICs. This review discusses (1) how HCV promotes genesis of TICs and HCC development; (2) how this process avails itself as a novel therapeutic target for HCC treatment; and (3) ten hall marks of TIC oncogenesis and HCC development as targets for novel therapeutic modalities.